Models of Emergency Psychiatric Services That Work - Fitz-Gerald, Mary Jo.; Takeshita, Junji; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book describes a spectrum of possible solutions to providing comprehensive emergency psychiatric care. It discusses in detail all components of emergency psychiatric care, such as triage, security, management of suicide risk, violent patients, interdisciplinary treatment teams, administration, and telepsychiatry. It has been written by and is of interest to psychiatrists, emergency medicine physicians, nurses, social workers, administrators, the police and security staff.
Introduction -- Systems of Emergency Psychiatric Coverage (Overview) -- Physical construction of psychiatric emergency services -- Interdisciplinary staffing and training requirements -- Telepsychiatry -- Security Aspects of Emergency Psychiatric Coverage -- Capacity -- Child and Adolescents in the psychiatry emergency room -- Geriatric patients in the psychiatry emergency room -- Developmentally disabled patients in the psychiatry emergency room -- Administration input.
Keywords: Psychiatry; Emergency medicine; Nursing; Psychiatry; Emergency Medicine; Nursing